Design of Onion Epidermis Peeling and Onion Smoothing Machine with Rubber Friction Method Application - Fadwah Maghfurah; Riki Effendi; Mochammad Nurul Aini (Jurnal POLIMESIN, 2020)
Onions are the main ingredients for all types of cuisine so the level of demand is quite high. In the industrial world, a great number of processes of onion epidermis peeling are still using either manual and simple low capacity methods or high capacity machines with expensive components. Therefore, it is necessary to make a high capacity machine to peel the onion epidermis in a short time by using inexpensive and durable components that are designed with the help of Solidworks software. The onion epidermis peeling and smoothing machine uses a  0.5 HP electric motor power as a bond drive and  a rubber friction method for the process of peeling the onion epidermis. Besides, this machine is also designed to be compatible with peeling by connecting the rotation of the motor that is directly connected to the electric motor so that its design is simpler and does not require a long cycle of time. This peeling process is able to peel 2 kg of onion in 3 minutes and 0.5 kg for the refinement process in 5 minutes.